US and cross-national policies, practices, and preparation implications for successful instructional leadership, organizational learning, and culturally responsive practices - Ylimaki, Rose M.; Jacobson, Stephen L. (Studies in educational leadership, 2011)
This book provides theories and empirical case study examples of instructional leadership, organizational learning, and culturally responsive practices as they are shaped by political, economic, and cultural factors in seven different national contexts. The seven countries featured in this book are the U.S., Australia, Denmark, England, Sweden, Norway, and Cyprus. The book begins with an overview of the ISSPP, including its underlying theoretical framework, its research methodologies employed, its limitations and how analyses of the project's data and findings evolved from the first phase of the study to its current focus.